Individual cognitive empowerment and in-role performance: a matched-pair study - Kimpah, Jeniboy; Rothmann, Sebastiaan; Ibrahim, Hazril Izwar; Jaaffar, Amar Hisham; Vinahapsari, Cinthia Annisa; Wider, Walton; Naces Udang, Lester (Frontiers in Psychology, 2024)
The study examines the model fit of individual cognitive empowerment, which includes psychological and environmental factors, and investigates the direct effect of environmental empowerment specifically work methods, work criteria, and work schedules on i n-role performance in Malaysia's E&E manufacturing firms. Data were obtained from 173 engineers and 173 managers, matched in pairs, who have worked together for at least one year in 73 E&E manufacturing firms. The study found that the model fit of psychological and environmental factors is stronger for individual cognitive empowerment. Work methods show a positive direct effect on in-role performance. However, work schedules and work criteria do not appear to have a direct effect on in-role performance. This study highlights the importance of considering work methods in the engagement between engineer and manager pairs in the E&E manufacturing sector to enhance in-role performance.